The Impact of International Trade and Globalization on Economic Growth, Employment, and Income Distribution - Xu, Zhandong (Transactions on Economics, Business and Management Research, 2024)
This essay delves into the profound impact that globalization and international trade have on economic growth, employment, and income distribution. By examining the case of DJI, a prominent Chinese company that has achieved significant success on the international stage, we gain insights into how local firms can expand their influence beyond domestic markets. DJI's rise as a global leader in the drone industry not only showcases its innovative capabilities but also serves as a catalyst for other Chinese companies aspiring to enter international markets. This phenomenon highlights the importance of globalization in fostering economic dynamism, as companies like DJI pave the way for increased competition, technological advancements, and job creation on a global scale. Moreover, the essay explores the reasons why international trade and globalization are crucial drivers of economic growth. By opening up markets and enabling the free flow of goods, services, and ideas across borders, globalization helps economies to capitalize on comparative advantages, leading to more efficient production and resource allocation. This, in turn, boosts overall economic output, improves living standards, and contributes to a more equitable distribution of wealth. Through the lens of DJI's success, the essay underscores the symbiotic relationship between international trade, globalization, and sustained economic growth.